2006
DOI: 10.1021/ja065434u
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organized Ureido Substituted Diacetylenic Organogel. Photopolymerization of One-Dimensional Supramolecular Assemblies to Give Conjugated Nanofibers

Abstract: The introduction of the urea function as structure directing agent of diacetylene organogels (DA-OGs) has been achieved. Despite the urea function being one of the most frequently used structure directing agents for the formation of organogels, it has never been exploited in the fabrication and photopolymerization of DA-OGs. The self-association of ureas involving two hydrogen bonds is much stronger than that of urethanes or amides, and the resulting supramolecular assemblies are completely insoluble. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
131
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(134 citation statements)
references
References 36 publications
3
131
0
Order By: Relevance
“…In a study by Weiss et al, a chiral amide-containing poly(diacetylene) was found to form blue left-handed quadruple helices in solution, which convert to red righthanded double helices and yellow isolated fibrils upon the addition of trifluoroacetic acid. 295 Similarly, Dautel et al reported that a polymer derived from a urea-functionalised butadiyne forms a blue gel in cyclohexane but converts to a red gel when heated to 130 o C, with a purple intermediate observed at 40 o C. 296 Whilst the blue-to-purple transition is irreversible and associated with a thermodynamic relaxation of the hydrogen bonded network, the purple-to-red transition is reversible until the temperature reaches 120 o C, whereupon the molecules adopt a non-hydrogen-bonded packing arrangement. Effects of this nature arise due to changes in the spacing and relative orientations of π systems and are thus strongly influenced by molecular geometry.…”
Section: Coupling Reactionsmentioning
confidence: 99%
“…In a study by Weiss et al, a chiral amide-containing poly(diacetylene) was found to form blue left-handed quadruple helices in solution, which convert to red righthanded double helices and yellow isolated fibrils upon the addition of trifluoroacetic acid. 295 Similarly, Dautel et al reported that a polymer derived from a urea-functionalised butadiyne forms a blue gel in cyclohexane but converts to a red gel when heated to 130 o C, with a purple intermediate observed at 40 o C. 296 Whilst the blue-to-purple transition is irreversible and associated with a thermodynamic relaxation of the hydrogen bonded network, the purple-to-red transition is reversible until the temperature reaches 120 o C, whereupon the molecules adopt a non-hydrogen-bonded packing arrangement. Effects of this nature arise due to changes in the spacing and relative orientations of π systems and are thus strongly influenced by molecular geometry.…”
Section: Coupling Reactionsmentioning
confidence: 99%
“…2,3 The chromatic transition of PDA can be directly detected by the naked eye, enabling a broad spectrum of optoelectronic and sensing applications. [4][5][6][7][8][9] However, the available PDA materials oen suffer from a slow response time (tens of seconds to minutes), low reversibility (tens of cycles or even irreversible), a narrow working temperature range (less than 90 C without the introduction of inorganic components) and poor mechanical properties, mainly due to the relatively low structural regularity and strength of molecular interactions. Based on the same reasons, the available chromatic polymers have generally been made into powders or lms, and it remains challenging to achieve continuous bres that are required for wearable electronics, which are a promising direction in sensing applications.…”
mentioning
confidence: 99%
“…Despite a wide range of reported responsive materials, the mostly used stimuli involve light, [5] reaction, [2] and heat. [6] However, it should be noted that development of a smart or adaptive gel which can be controlled or even switched by sound [7] and thixotropy [8] is also very appealing.…”
mentioning
confidence: 99%